Observer‐based tracking control for constrained nonlinear systems with mismatching disturbances and its application. (5th October 2020) - Min, Huifang; Xu, Shengyuan; Fei, Shumin; Cui, Guozeng; Tan, Yushun
Summary: In this article, a novel output‐feedback control scheme is proposed for nonlinear systems involving unknown input saturation, control gain, and unmeasurable disturbances under the condition of an output constraint. First, a proper barrier Lyapunov function and an opportune backstepping are used to alleviate the control burdens caused by output constraint. Then, a novel auxiliary system is introduced with appropriate coordinate transformation, which can create extra freedoms to attenuate the effects brought by input saturation. As a remarkable feature, a composite observer with the estimate of unknown control gain is constructed on the basis of disturbance observer‐based control and state observer control. It can deal with the unmeasurable disturbances and states simultaneously. According to the proposed scheme, it is proven that all the signals in the closed‐loop system are uniformly ultimately bounded, and the tracking error is bounded by the design parameters and saturated input error without the violation of the output constraint. Finally, the effectiveness of the proposed control is verified by two simulation examples.